Influence of MWCNT/surfactant dispersions on the mechanical properties of Portland cement pastes (2017)
This work studies the reinforcing effect of Multi Walled Carbon Nanotubes (MWCNT) on cement pastes. A 0.35% solid concentration of MWCNT in powder was dispersed in deionized water with sodium dodecyl sulfate (cationic surfactant), cetylpyridinium chloride (anionic surfactant) and triton X-100 (amphoteric surfactant) using an ultrasonic tip processor. Three concentrations of each surfactant (1mM, 10mM and 100mM) were tested, and all samples were sonicated until an adequate dispersion degree was obtained. Cement pastes with additions of carbon nanotubes of 0.15% by mass of cement were produced in two steps; first the dispersions of MWCNT were combined with the mixing water using an ultrasonic tip processor to guarantee homogeneity, and then cement was added and mixed until a homogeneous paste was obtained. Direct tensile strength, apparent density and open porosity of the pastes were measured after 7 days of curing. It was found that the MWCNT/surfactants dispersions decrease the mechanical properties of the cement based matrix due to an increased porosity caused by the presence of surfactants. © Published under licence by IOP Publishing Ltd.